Effect of Draw Ratio on Physical, Release, and Antibacterial Properties of Poly(ε‐caprolactone) Loaded with Lysozyme. Issue 12 (14th November 2017) - Bugatti, Valeria; Acocella, Maria Rosaria; Maggio, Mario; Vigliotta, Giovanni; Pantani, Roberto; Gorrasi, Giuliana
Abstract: In this work, some films of poly(ε‐caprolactone) (PCL) containing lysozyme at 5% by weight are obtained. Lysozyme is a natural antimicrobial molecule. The films are submitted to cold drawing process at three different draw ratios, λ = 3, 4, and 5, where λ is the ratio between final and initial length. Morphology, physical and barrier properties of the drawn samples are studied and correlated to the release of lysozyme. Tests against Bacillus sp are performed and correlated to the material texture. The molecular orientation of uniaxially drawn lysozyme doped PCL films is demonstrated to be a significant parameter for controlled release monitoring of the active molecule and the antimicrobial activity. Abstract : Poly(ε‐caprolactone) and lysozyme are submitted to draw processing at different draw ratios. The release of lysozyme is studied and found dependent on the draw ratio. The relationship between release rate and antimicrobial activity is also investigated. The macromolecular chain orientation is demonstrated to be an interesting and easy tool for the achievement of desired controlled release systems.